1996
DOI: 10.1002/(sici)1099-0488(19960115)34:1<75::aid-polb5>3.3.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Stress‐enhanced transport of toluene in poly aryl ether ether ketone (PEEK)

Abstract: SYNOPSISThe transport of fluids in the semicrystalline polymer, poly(ary1 ether ether ketone) (PEEK), was investigated. Both solubility and rate of penetration of toluene into PEEK are markedly increased by the application of an external stress. The induction period (i.e., the time for the sorption to begin) is a function of applied stress as well as temperature and crystallinity. At 22°C in 29% crystalline PEEK the induction period was reduced from more than 2000 h to approximately 10 h whereas the solubility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 0 publications
4
14
0
Order By: Relevance
“…The breakthrough time has been experimentally correlated to the thickness of the membrane for various polymer‐solvent systems, so the trend predicted by eq. (21) also agrees with experimental data as transport through thinner membranes exhibits shorter breakthrough times 11, 14…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The breakthrough time has been experimentally correlated to the thickness of the membrane for various polymer‐solvent systems, so the trend predicted by eq. (21) also agrees with experimental data as transport through thinner membranes exhibits shorter breakthrough times 11, 14…”
Section: Discussionsupporting
confidence: 83%
“…The increase in flux is in agreement with experimental data, as a larger γ 2 implies a larger effect of E , the elastic diffusion coefficient, on the transport of chemicals through polymeric membranes. This prediction may be useful in explaining previously reported cases of stress‐enhanced transport 10, 11, 14. An increase in γ 2 also increases the time to reach a maximum flux.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…They attributed this difference to irreversible structural changes of the HDPE. 12 This study found that the solubility and rate of diffusion into the resin are greatly increased by the application of stress. The HDPE film is gradually transformed into a fibrillar structure, substantially reducing the number of sorption sites.…”
Section: Effect Of Mechanical Deformation On Permeationmentioning
confidence: 97%
“…This is consistent with the results of Choy et al, 78 who found that high draw ratios induce structural changes in polyethylene. 12 Other studies have observed that external stress, either uniaxial tensile stress or fabrication residual stress, produced an enhanced equilibrium solubility and an accelerated rate of diffusion, 83,84 however, none of these studies performed the permeation or solubility experiments when the membranes were in a state of deformation. Drummond et al 79 used atomic force microscopy (AFM) to study the structural changes due to external deformation.…”
Section: Effect Of Mechanical Deformation On Permeationmentioning
confidence: 99%